DEVELOPING OF ENGLISH VOCABULARY POCKET BOOK MULTIMEDIA GRADE TENTH AT STATE 3 VOCATIONAL HIGH SCHOOL METRO - Suhono; Rani Setyawati; Wiwied Pratiwi (International Journal on Integrated Education, 2023)
This research develops multimedia vocabulary media pocket books in English which aims to determine the validity of multimedia vocabulary media pocket books in English, determine the practicality of multimedia vocabulary media pocket books in English, and determine the effectiveness of multimedia vocabulary media pocket books in English. The purpose of this study was to improve multimedia vocabulary mastery in English and increase students' interest in reading by using pocket books for tenth grade students at State Vocational High School 3 Metro. Researchers used RND research. Data collection was carried out through observation, interviews, questionnaires and documentation. This development uses the Borg & Gall model where there are 10 steps, but only 6 steps are used due to time, effort and cost limitations. The validity results obtained were 98.3% (media experts) and 98.47% (material experts), (2) the practicality of the media was stated to be very practical with a percentage of 97% (student questionnaire), and the effectiveness of the media was stated to be very effective with the results of the learning percentage of 90% (evaluation).